Occurrence and background of wild oats [Avena fatua] and Italian ryegrass [Lolium multiflorum] in winter cereals in the Kanto-Tokai region [Japan] - Asai, M.(National Agricultural Research Center, Tsukuba, Ibaraki (Japan)); Yogo, Y (Journal of Weed Science and Technology, 2005)
An investigation into the occurrence of wild oats and Italian ryegrass in winter cereal fields in the Kanto-Tokai region was conducted by questionnaires to agricultural extension service offices (AESO) and annual field surveys. Wild oats and Italian ryegrass were found in all prefectures; half of the AESO that replied observed infestation in winter cereal fields. 'Severe infestation' was reported from Saitama and Ibaraki prefectures for wild oat, and Saitama and Shizuoka prefectures for Italian ryegrass. Paddy rice was not part of crop rotation in such fields. Field monitoring confirmed that wild oats tend to dominate fields in which winter cereals had been cropped annually until fields were left fallow or were planted other crops because of weed loss. These weeds were assumed to have escaped from fodder crops, manures and revegetation materials. Field surveys detected no tame oat infestations. Continuous winter cereal cropping, as well as lack of effective control methods, were assumed to be involved in the spread of weeds into the fields. This result suggests that there is a growing threats of by winter grass weeds in locations where field conversion from paddy to upland is promoted.